A Case for Regional Seismic Reflection Surveys in the Gawler Craton, South Australia - Okan, E.; Kepic, Anton; Urosevic, M.; Ziramov, S. (Australian Society of Exploration Geophysicists, 2015)
The seismic reflection method provides the possibility for delineation of very complex geological and this method might be good for detecting the presence of Iron Oxide Copper-Gold (IOCG) deposits. Despite many technically superior attributes, no arguments for regional seismic exploration have been proposed; probably because a cost-benefit analysis has never been conducted at such a scale. In this study we analyse such a case by modelling a Hillside IOCG deposit scenario where 2D seismic with relatively sparse source-receiver geometry is used to detect the presence of a possible intrusive package near a deep fault. The modelling results show that seismic reflection using 20m geophones and 40m shot spacing as an exploration tool is feasible, and that with the spacing halved we can definitely recover reasonable images of the upper parts of the mineralisation. The presences of such intrusives are clearly detectable and with the seismic method are detectable from 100m to 1000m deep. Thus, we propose that using 2D seismic is viable for IOCG exploration as it can detect mineralised intrusive structures along known favourable corridors or structures.